2019
DOI: 10.29333/iejme/5937
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Learning Strategies in Mathematics Classroom Intervention: A Review of Implementation and Operational Design Aspect

Abstract: Mathematical learning is to produce a high competence individual with multiple skills in line with the needs of the 21st century. However, mathematical education is still plagued with problem of mastery of mathematical concepts. In addressing this problem, various initiatives and interventions need to be implemented to ensure that mathematical mastery is at the normal and best level. Metacognitive Learning Strategies (MLS) can be used as interventions to tackle weak issues of mastery. The strength of MLS is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Findings signify that the use of metacognitive strategies like thinking aloud and journal writing is better than the traditional teaching strategies in improving the performance and problem-solving skills of the students. This finding was supported by [1] statements that metacognitive learning strategies can be used as intervention that help the students to attain mastery.…”
Section: Posttest Scores Of the Control And Experimental Groupmentioning
confidence: 63%
See 1 more Smart Citation
“…Findings signify that the use of metacognitive strategies like thinking aloud and journal writing is better than the traditional teaching strategies in improving the performance and problem-solving skills of the students. This finding was supported by [1] statements that metacognitive learning strategies can be used as intervention that help the students to attain mastery.…”
Section: Posttest Scores Of the Control And Experimental Groupmentioning
confidence: 63%
“…However, many students have difficulty in learning Basic Calculus because majority of the junior high school students entering in the senior high school have weak performance in mathematics. [1] stated that mathematical education is still plagued with problems in terms of mastery of mathematical concepts. This statement revealed that the competencies needed in taking the Basic Calculus were possibly not attained.…”
Section: Introductionmentioning
confidence: 99%
“…Students need to have metacognitive competences in their learning activities. This is reinforced by the results of some researches which states that metacognitive competencies have an essential role in managing and controlling the cognitive processes of individuals in learning activities and in having them to think more effectively and efficiently, also to train students to develop learning strategies and determine solutions in solving problems (Bakar and Ismail, 2019;Bran and Balas, 2011;Chen et al, 2019;Iskandar, 2014;Kartika and Sujadi, 2015;Christian, 2015;Künsting et al, 2013;Kyriakides et al, 2020;Pintrich, 2002;Romli, 2012;Sastrawati and Rusdi, 2011;Taub et al, 2020;Vrieling et al, 2012;Zheng et al, 2019) The result of this study supports a prior study by Wardany and Ramli (2017), which showed that HOTS assessment instrument products in the form of developed multiple choice and essays have validity and reliability with very high average interpretation and good quality questions in terms of the level of difficulty and discrimination index. Indeed, Sari (2018) also revealed that the feasibility of metacognitive-based and HOTS-oriented Student Activity Sheet, which assessed material aspects, linguistic aspects, and visual aspects, met decent criteria even the product was suitable for use, both for different learning or research.…”
Section: Question Differentiation Index Resultsmentioning
confidence: 99%
“…Metacognitive strategies will stimulate students to think of alternative strategies for solving mathematical problems (Tachie, 2019). Metacognitive strategies can also encourage students to find, think, compare, and even predict possibilities in future conditions (Bakar & Ismail, 2019). Furthermore, Waskitoningtyas (2015) explained that metacognitive strategies could design, monitor, and control what students know, what students need to do, and how to do it so that students realize when they understand and when they do not understand concepts in learning.…”
Section: Metacognitive Approachmentioning
confidence: 99%